(untitled) (Journal of the College of Basic Education, 2022)
research basically aims to identify the relationship between social Extremism and distressing childhood experience among middle school. The research sample reached (100) students from preparatory schools in Aby-Grab. Al-karkh, the tow researchers reached the following results: 1-none of the among school students social Extremism. 2- none of the among school students distressing childhood experience 3-there is a relationship between social Extremism and distressing childhood experience although they are not found in the research sample.